Laboratory-based characterization of shallow silty soils in southwest Christchurch. Issue 110 (July 2018) - Beyzaei, Christine Z.; Bray, Jonathan D.; Cubrinovski, Misko; Riemer, Michael; Stringer, Mark
Abstract: Cyclic triaxial test data are presented to characterize the cyclic response of silty soils at three no-liquefaction case history sites in southwest Christchurch. Stress-strain response and axial strain accumulation demonstrate nuanced, transitional responses of silty soils. Post-liquefaction reconsolidation volumetric strains are within the range expected for clean sands. However, there are clear differences in the post-liquefaction response of silts from that of sands. Low-plasticity silts undergo time-dependent reconsolidation whereas sands undergo immediate reconsolidation. Simplified liquefaction triggering procedures estimate significant liquefaction at these sites; yet, no liquefaction manifestations were observed during the Canterbury earthquake sequence. Laboratory estimates of cyclic resistance are consistent with estimates from simplified liquefaction triggering procedures, and both estimates are well below the estimated seismic demand. Thus, liquefaction is likely triggered at the element-level in the silty soil deposits. Post-liquefaction reconsolidation test results suggest water and ejecta may not necessarily accumulate in these stratified silty soils as they would accumulate in thick deposits of liquefiable clean sands. Thus, manifestations of liquefaction may not be observed at stratified silt/sand sites with delayed reconsolidation responses and lower hydraulic conductivities. Additional mitigating factors may also have contributed to the discrepancy between simplified procedure estimates of liquefaction and the lack of liquefaction observed at these sites. Highlights: Liquefaction expected, but no manifestations in the Canterbury earthquake sequence. Cyclic triaxial tests performed to characterize cyclic response of the silty soils. Laboratory-based cyclic resistance consistent with CPT-based procedure estimates. Silty soil cyclic responses differed significantly from those of clean sand. Factors such as soil layering and impeded drainage may have prevented manifestation.